PERLINDUNGAN HUKUM TERHADAP ANAK DALAM EKONOMI ISLAM: PENGELOLAAN HARTA DAN SANTUNAN - Putri Sinlae, Ester Stevany; Syahda, Illa Fatika; Putra, Rizki Dwi; Syifa, Tazkia Suhaila; Fauzi, Muhammad; Mahipal, Mahipal (IAIN BONE, 2024)
Abstract Life is something noble and very precious. Humans are social creatures who cannot live without the help of others. In addition, humans also have a higher level than other creatures. Islam recommends giving charity to orphans, especially if they are poor. In addition to orphans who are poor, we must also pay attention to orphans whose parents leave them an inheritance. Orphans need a guardian who is able to care for and protect them. The guardian's duty is to look after the orphan, feed him, and provide for his needs if he has no property, and look after him if he has property. The guardian can manage the orphan's property by keeping it as a trust or managing it himself. Orphaned property is something useful and valuable that is owned by a child who does not have a parent (father). The status of orphaned property is not much different from the status of property in general in Islam, which is very important in life, especially for orphans themselves. In addition to managing and maintaining, guardians are also obliged to educate orphans until they are mature and able to maintain their own property. Once they (orphans) are adults then the guardian is obliged to hand over their property and preferably in the presence of witnesses. Orphanages are social institutions that have a mission to protect and foster orphans, orphans, abandoned people, and the poor for the welfare of their foster children. This is because children are the main foundation that determines the future life of a nation, therefore it is necessary to prepare the next generation of the nation by preparing children to grow and develop optimally both morally, physically / motorically, cognitively, linguistically and socially emotionally. In the mechanism of sharing profits and the risk of loss is borne together according to the mudharabah contract, namely the profits and losses are borne together according to the agreement agreed upon at the beginning of the contract. Managing orphan assets according to Islamic law is not prohibited by religion, as long as it is done with good intentions and goals, not to harm or destroy. Abstrak Kehidupan adalah sesuatu yang mulia dan sangat berharga. Manusia merupakan makhluk sosial yang tidak dapat hidup tanpa bantuan orang lain. Selain itu, manusia juga mempunyai tingkatan yang lebih tinggi dibandingkan makhluk lainnya. Islam menganjurkan bersedekah kepada anak yatim, terutama jika mereka miskin. Selain anak yatim piatu yang tidak mampu, kita juga harus memperhatikan anak yatim piatu yang orang tuanya mewariskan warisan. Anak yatim memerlukan wali yang mampu merawat dan melindunginya. Kewajiban wali adalah memelihara, memberinya makan, memenuhi kebutuhannya jika anak tersebut tidak mempunyai harta benda, dan menjaga serta merawatnya jika anak tersebut mempunyai harta benda. Wali dapat mengelola harta anak yatim dengan cara menyimpannya sebagai titipan atau mengelolanya sendiri. Harta yatim adalah sesuatu yang berguna dan berharga yang dimiliki oleh anak yang tidak mempunyai orang tua (ayah). Status harta anak yatim tidak jauh berbeda dengan status harta pada umumnya dalam Islam, yaitu sangat penting dalam kehidupan khususnya bagi anak yatim itu sendiri. Selain mengelola dan memelihara, wali juga wajib mendidik anak yatim hingga dewasa dan mampu memelihara harta bendanya sendiri. Setelah mereka (anak yatim) dewasa maka wali wajib menyerahkan harta mereka dan sebaiknya di hadapan saksi. Panti Asuhan adalah lembaga sosial yang mempunyai misi melindungi dan membina anak yatim, anak yatim piatu, orang terlantar, dan kaum dhuafa demi kesejahteraan anak asuhnya. Hal ini dikarenakan anak merupakan landasan utama yang menentukan masa depan kehidupan suatu bangsa, oleh karena itu perlu dilakukan penyiapan generasi penerus bangsa dengan mempersiapkan anak untuk tumbuh dan berkembang secara optimal baik secara moral, fisik/motorik, kognitif, bahasa dan sosial emosional. Dalam mekanisme pembagian keuntungan dan resiko kerugian ditanggung bersama menurut akad mudharabah, yaitu keuntungan dan kerugian ditanggung bersama menurut kesepakatan yang telah disepakati pada awal akad. Mengelola harta anak yatim menurut hukum Islam tidak dilarang oleh agama, sepanjang dilakukan dengan niat dan tujuan yang baik, tidak merugikan atau membinasakan.